Prevalence of viral hepatitis B and C infection and associated factors among pregnant women in southeast Ethiopia: community-based crossectional study - Nuruzelam Mohammed; Jeylan Kassim; Ahmednur Adem Aliyi; Muhammed Jemal Abdurebi (Frontiers in Global Women's Health)
IntroductionHepatitis B or C infection during pregnancy increases the risk of vertical transmission, which is risky for the growing fetus and the newborn. In order to prevent such adverse effects and outcomes, it is crucial to understand the scope of the problem. However, absence of data on community-based Prevalence of viral hepatitis among pregnant women and conflicting evidence from facility-based study shows there is paucity of information on seroprevalence of Hepatitis B and C virus infection among pregnant women.MethodsA community-based cross-sectional study was conducted on 422 pregnant women selected from three selected kebeles of Robe town. Study participants were selected using systematic sampling technique. Data were collected through pretested interviewer administered questionnaire and three milliliter blood sample were collected and tested for HBsAgn and Anti-HCV Antibodies. Descriptive statistics such as frequency, mean, and standard deviation were used to summarize data. Binary logistic regression was used to identify factors associated with occurrence of Hepatitis B and C virus among pregnant women. Accordingly, variables with P value < 0.25 in bivariate logistic regression were declared as candidate for multivariable logistic regression. From multivariable logistic regression adjusted odds ratio with 95% confidence interval were computed. Those variable with p- value <0.05 were declared as factor associated with dependent variable.Results and discussionA total of 410 pregnant women participated in the study, which yielded a response rate of 97.2%. The seroprevalence of hepatitis B and C virus infections was found to be 7.6%, and 2.2% respectively, whereas one (0.24%) woman was co-infected. History of dental extraction (AOR = 2.70, 95% CI 1.09, 6.69), hospital admission (AOR = 6.96, 95%CI 1.73, 27.99), household contact (AOR = 3.93, 95% CI 1.37, 11.25), tattooing (AOR = 3.50 95% CI 2.31, 12.35), sexually transmitted infection (AOR = 11.42 95% CI 3.10, 42.35) were significantly associated with HBsAg infection whereas history of blood transfusion (AOR 5.58, 95% CI 1.03, 30.05, P = 0.045) and household contact (AOR 7.49, 95% CI 1.34, 41.76) were significantly associated with HCV infection among pregnant women.ConclusionsThe Seroprevalence of HBV and HCV was moderate endemicity according to WHO classification. Finding from present study shows different factors that plays great role in transmission of viral hepatitis.